Durability testing of fine grained stabilised soils - Notman, C.F. (2011)
Lime and/or cement stabilised fine-grained soils have been successfully used in the construction industry throughout the UK since the early 1970’s. Soil stabilisation has several economic, technical and environmental advantages. Although the vast majority of roads built upon stabilised soil foundations have resulted in durable pavements, a few case studies exist where expansive reactions have locally occurred, resulting in the requirement for extensive remedial works. Two high profile failures attributed to the expansion of stabilised capping layers were the M40 Banbury IV contract and the more recently constructed A10 Wadesmill Bypass. Both were Department for Transport (DfT) contracts in which the California Bearing Ratio (CBR) swell test was used as part of the quality control and/or investigation procedure. The Highways Agency (HA) and the Transport Research Laboratory (TRL) are still recommending the use of the CBR swell test as a means of determining a soils suitability for use within the stabilised process.